2019
DOI: 10.1017/s0029665119000934
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics and constipation: mechanisms of action, evidence for effectiveness and utilisation by patients and healthcare professionals

Abstract: The aim of this narrative review is to assess and present evidence on the mechanisms of action of probiotics in constipation, their effectiveness and their utilisation by patients and healthcare professionals. Chronic constipation is a common bothersome disorder that has a considerable impact on patients' quality of life. Probiotics have been increasingly investigated for their effectiveness in various disorders, including chronic constipation. Probiotics may affect gut motility and constipation through their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 75 publications
(115 reference statements)
1
37
0
1
Order By: Relevance
“…There are several animal and human studies suggesting that probiotics may regulate gut motility and improve constipation-related outcomes via their impact on the gut microbiota and their by-products, and on the nervous and immune system [63][64][65].…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several animal and human studies suggesting that probiotics may regulate gut motility and improve constipation-related outcomes via their impact on the gut microbiota and their by-products, and on the nervous and immune system [63][64][65].…”
Section: Probioticsmentioning
confidence: 99%
“…There are several animal and human studies suggesting that probiotics may regulate gut motility and improve constipation‐related outcomes via their impact on the gut microbiota and their by‐products, and on the nervous and immune system [63–65]. Systematic reviews have demonstrated variable results for different probiotic strains in both children [66, 67] and adults [68].…”
Section: Manipulating the Microbiomementioning
confidence: 99%
“…Irritant drugs have limited efficacy and serious adverse effects ( Bharucha et al, 2017 ; Luthra et al, 2019 ). Therefore, oral supplementation with probiotics (safe and long-acting) is attracting considerable interest among gastrointestinal physicians and researchers ( Dimidi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors included 56 patients with constipation, randomized to receive L. reuteri for 105 days. Dimidi et al [ 43 , 44 ], in their review on the mechanisms of action of probiotics on the gut motility and constipation, and the interaction with the gastrointestinal microbiota, demonstrated that L. reuteri interacts with the gut-brain axis and modulates the afferent sensory nerves that influence gut motility. Moreover, it involves the enteric nervous system, increasing the excitability of myenteric neurons in rats through action on the 5-HT pathways.…”
Section: Introductionmentioning
confidence: 99%